2009
DOI: 10.1177/105268460901900204
|View full text |Cite
|
Sign up to set email alerts
|

Leadership Practices for Social Justice, Democratic Community, and Learning: School Principals’ Perspectives

Abstract: The purpose of this qualitative study was to discover leadership practices that integrate social justice and democratic community for student learning. Data were gathered through focus group discussions with school principals. The responses were transcribed verbatim, coded, and analyzed for emerging themes. Leadership practices that were identified as themes in this study included shared decision making, advocacy, dispositions and relationships, and social control with purpose. Participants perceived public pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(32 citation statements)
references
References 16 publications
0
29
0
3
Order By: Relevance
“…Further research has shown that principals committed to social justice engage in advocacy work (Jean-Marie, 2008). Advocacy includes grooming teacher leaders with social justice orientations, engaging in democratic decision-making processes, using data (qualitative and quantitative) to raise concerns, mediating conflicts and misconceptions, addressing deficit perspectives or toxic school cultures, and championing social justice-oriented principles (Theoharis, 2007;Theoharis & O'Toole, 2011;Wasonga, 2009). For principals working in high-poverty urban schools seeking to create more inclusive schools, advocacy work might include the development of an interdisciplinary teacher team that will advocate for inclusion and generate new strategies to support inclusive education.…”
Section: Incorporating Teachers Into Leadership Activities and Rolesmentioning
confidence: 96%
See 1 more Smart Citation
“…Further research has shown that principals committed to social justice engage in advocacy work (Jean-Marie, 2008). Advocacy includes grooming teacher leaders with social justice orientations, engaging in democratic decision-making processes, using data (qualitative and quantitative) to raise concerns, mediating conflicts and misconceptions, addressing deficit perspectives or toxic school cultures, and championing social justice-oriented principles (Theoharis, 2007;Theoharis & O'Toole, 2011;Wasonga, 2009). For principals working in high-poverty urban schools seeking to create more inclusive schools, advocacy work might include the development of an interdisciplinary teacher team that will advocate for inclusion and generate new strategies to support inclusive education.…”
Section: Incorporating Teachers Into Leadership Activities and Rolesmentioning
confidence: 96%
“…Principals seeking to establish more socially just schools must address special education and the disproportionate representation of African Americans in segregated, special-education placements (DeMatthews & Mawhinney, 2014), but each school has different situations, individuals, cases, and contexts that make it difficult to define or describe prior to the principal engaging in leadership practices (Bogotch, 2002;McKenzie et al, 2008). Generally, social justice leadership involves: (a) interrogating school policies, cultures, and community expectations; (b) identifying oppressive and unjust practices; (c) employing democratic processes to engage marginalized communities (Wasonga, 2009); and (d) substituting unjust practices with equitable and culturally appropriate ones (Dantley & Tillman, 2006;Furman, 2012;Theoharis, 2007;Theoharis & O'Toole, 2011). In the process, leadership must be inclusive:…”
Section: Inclusion and Social Justice Leadershipmentioning
confidence: 98%
“…Similarly, justice-oriented forms of leadership may also have origins in the American Civil Rights movement (Lewis 2016). During (and before) the Civil Rights movement, Black educational leaders acknowledged that traditional forms of schooling and school leadership were reproducing injustices for Black students and their communities (Wasonga 2009). To promote justice, Black educational leaders reenvisioned purposes of school leadership as "fighting to overcome the social barriers of poverty and class, slavery, and institutionalized racism's inequities within a democratic society" (Murtadha and Watts 2005, p. 592).…”
Section: Social Justice Leadership Justice-oriented Forms Of School Lmentioning
confidence: 99%
“…Other forms of justice-oriented leadership are conceptualized more in terms of processes rather than specific groups, although all emancipatory leadership forms keep traditionally-marginalized students at their center. Democratic leadership focuses on including all school and community stakeholders in decision-making, and envisioning the school as crucial to promoting critical citizens' participation in a democracy (Anderson and Cohen 2018;Furman 2012;Wasonga 2009). Similarly, transformative leadership is focused on democratic decision-making and working with school stakeholders to transform school communities toward a more sociallyjust state of being (Quantz et al 1991;Shields 2004).…”
Section: Social Justice Leadership Justice-oriented Forms Of School Lmentioning
confidence: 99%
“…interrogate school and community expectations, policies and practices, and utilize democratic processes to change the status quo in targeted schools (Wasonga, 2009).…”
Section: On Social Justice Leadershipmentioning
confidence: 99%